Lung specific stealth liposomes: stability, biodistribution and toxicity of liposomal antitubercular drugs in mice - Deol, Parampal; Khuller, G.K (Biochimica et biophysica acta, 1997)
Liposomes with enhanced affinity towards lung tissue were prepared for the development of more effective chemotherapy against tuberculosis. Modification of surface of stealth liposomes by tagging O-stearylamylopectin (O-SAP) resulted in the increased affinity of these liposomes towards lung tissue of mice. Liposomes containing egg phosphatidylcholine (ePC), cholesterol (CH), dicetylphosphate (DCP), O-SAP and monosialogangliosides (GM 1)/distearylphosphatidylethanolamine-poly(ethylene glycol) 2000 (DSPE-PEG 2000) were found to be most stable in serum. Tissue distribution of these liposomes showed more accumulation in lungs than in reticuloendothelial systems (RES) of normal and tuberculous mice. Pre administration of PC and CH (2:1.5) liposomes before the injection of lung specific stealth liposomes further enhanced their uptake in lungs. In vivo stability of these liposomes demonstrated the slow and controlled release of their encapsulated contents. Isoniazid and rifampicin encapsulated in liposomes were less toxic to peritoneal macrophages as compared to free drugs. Further, encapsulated drugs also demonstrated reduced in vivo toxicity in comparison to free drug(s). These findings suggest liposomes to be better drug delivery vehicles for experimental tuberculosis.